The impact of core training on overall athletic performance in different sports: a comprehensive meta-analysis - Yu, T.; Xu, Y.; Zhang, Z.; Sun, Y.; Zhong, J.; Ding, C. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background and objectives Despite widespread implementation of core training in athletic preparation, evidence regarding its effectiveness across different sports and performance domains remains fragmented. This meta-analysis examined the effects of core training on athletic performance across multiple sports, addressing limitations of previous analyses that focused on single sports or limited performance measures.